Factors Impacting Digital Accounting Systems Trend: Empirical Evidence from An Emerging Market - Tran, Ngoc Hung (International Journal of Membrane Science and Technology, 2023)
This study aims to investigate the factors that influence the digitalization of accounting systems applications in Vietnamese firms. The research focuses on the impact of Top Management Teams (TMTs), innovative corporate culture, Big Data, and Information Technology (IT) Infrastructure on the adoption of accounting systems applications. A comprehensive review of relevant literature reveals that TMTs play a critical role in driving digitalization initiatives, including accounting systems applications. Additionally, an innovative corporate culture can foster the adoption of digital technologies, leading to increased efficiency and accuracy of accounting systems. Moreover, the study identifies Big Data as a crucial resource for accounting systems, while IT Infrastructure is essential for successful implementation. Employing a quantitative survey methodology, the study collects data from 285 Vietnamese companies using purposive sampling techniques. The research findings provide insights into the factors that affect the digitalization of accounting systems applications in Vietnamese firms, which is beneficial for both practical management and theoretical perspectives.